Using a balanced scorecard to improve the financial perspective of an organisation : a case study of the Tshwane University of Technology Polokwane Campus - Vermaak, Frans N.S. (University of Pretoria, 2014)
Dissertation (MCom)--University of Pretoria, 2013.